Determination of Lactose Concentration in Low-Lactose and Lactose-Free Milk, Milk Products, and Products Containing Dairy Ingredients, Enzymatic Method: Single-Laboratory Validation First Action Method 2020.08. (16th March 2021) - Ivory, Ruth; Delaney, Elaine; Mangan, David; McCleary, Barry V
Abstract: Background: The AOAC Stakeholder Panel on Strategic Food Analytical Methods issued a call for methods for the measurement of lactose in low-lactose and lactose-free products under Standard Method Performance Requirement (SMPR ® ) 2018.009. Megazyme's Lactose Assay Kit (K-LOLAC) was developed specifically to address the need for accurate enzymatic testing in lactose-free samples. Objective: K-LOLAC was validated for measurement of lactose in low-lactose and lactose-free milk, milk products, and products containing dairy ingredients. A single-laboratory validation (SLV) of the method is reported. Method: K-LOLAC is an accurate and sensitive enzymatic method for the rapid measurement of lactose in low-lactose or lactose-free products. Validation analysis was performed on a sample set of 36 commercial food and beverage products and a set of 10 certified reference materials. Parameters examined during the validation included working range and linear range, selectivity, LOD, LOQ, trueness ( bias ), precision (repeatability and intermediate precision), robustness, and stability. Results: For all samples tested within the lower range (10–100 mg/100 g or mL), recoveries varied from 93.21–114.10%. Recoveries obtained for samples in the higher range (>100 mg/100 g or mL) varied from 94.44–108.28%. All materials had repeatability relative standard deviations (RSDr and RSDir ) of <9%. Conclusions: The commercial K-LOLAC assay kit, as developed by Megazyme, meets the requirements set out under SMPR 2018.009. Highlights: K-LOLAC is a robust, quick, and easy method for analysis of lactose in foodstuffs and beverages.